Unravelling Masculinity: Affect, Vulnerability and Melancholy in Nthikeng Mohlele’s Rusty Bell (2014) - Pawlicki, Marek (Journal of Literary Studies, 2025)
This article offers a close reading of Nthikeng Mohlele’s Rusty Bell (2014) from the perspective of masculinity studies and affect theory. Concentrating on the life of an upper-middle-class lawyer, Michael, Mohlele’s novel describes the psychological and moral crisis he faces as he tries to negotiate a place for himself within the existing social structures, specifically the family. Confronted with this task, Michael struggles with a sense of vulnerability that manifests itself most acutely in his interactions with others, particularly his wife, Rusty Bell, and his close friend, Christopher “Columbus” Wentzel. This article explores the close connection between emotional closeness and vulnerability, and indicates that intimacy can undermine rather than consolidate the self, including one’s gender identity. In Mohlele’s novel, intimacy, understood as physical closeness, is associated with emotional entrapment, which has its origins in Michael’s traumatic experience of sexual abuse. Equally importantly, intimacy is also bound with a profound feeling of sadness after the premature death of Michael’s friend. Following Judith Butler, I discuss this sadness as regards gender melancholy, which Michael experiences as he mourns the loss of his homosocial relationship with Columbus. The analysis of Mohlele’s novel is based on Lauren Berlant’s insights into intimacy, focusing on its failure to stabilise socially sanctioned forms of closeness. I also draw upon Todd Reeser’s approach to affect as a force capable of both composing and decomposing masculinity. By offering the first sustained critical discussion of Rusty Bell, this article aims to contribute to a wider debate on Black masculinities in post-apartheid literature.